2016
DOI: 10.1590/0103-8478cr20151571
|View full text |Cite
|
Sign up to set email alerts
|

Interception of solar radiation by the productive structures of spring canola hybrids

Abstract: The objective of this study was to adjust parameters related to the interception of photosynthetically active radiation (PAR) by reproductive structures of spring canola, with different nitrogen levels and hybrids. Two field experiments were conducted, being one with different sowing dates and hybrids (Hyola 61 and Hyola 432) and another with doses of 10, 20, 40, 80, 160kg ha -1 of N, applied in top dressing. They were conducted in Passo Fundo and Coxilha, RS, Brazil, in 2011 and 2014, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…When the temperature of the air rises above 27 °C, thermal stress occurs in the crop, reducing or even inhibiting the canola processes of growth and development, mainly in the final period of flowering and initial filling of the grains [12]. This is what happened to the fourth seeding season.…”
Section: Resultsmentioning
confidence: 99%
“…When the temperature of the air rises above 27 °C, thermal stress occurs in the crop, reducing or even inhibiting the canola processes of growth and development, mainly in the final period of flowering and initial filling of the grains [12]. This is what happened to the fourth seeding season.…”
Section: Resultsmentioning
confidence: 99%
“…The flower petals usually fall during maturation, but interception and absorption of photosynthetically active radiation (PAR) by siliques and stems may continue. Fochesatto et al (2016) evaluated the interception efficiency of PAR by canola reproductive structures and stems for five nitrogen doses (10,20,40,80, and 160 kg ha -1 N) and reported that the efficiency of PAR interception by the reproductive structures and stems of the canola canopy can reach 70% of the total canopy interception in the plots treated with 160 kg ha -1 N. Therefore, intrinsic characteristics of the canola crop, such as the intense flowering and the existence of photosynthesizing structures besides the leaves, make the interaction between the crop and solar radiation, as well as its detection by remote sensors, very specific. These characteristics are important and should be taken into account both for the differentiation of other crops and for the construction of grain yield estimation models.…”
Section: Resultsmentioning
confidence: 99%
“…The light use efficiency was affected by many factors, such as the gene, phenotype, environmental factors, and so on (Brunel-Muguet et al, 2013;Wang et al, 2015;Singh et al, 2018). As previous papers concluded, the plant canopy composed of leaves, stems, branches and pods was the main place for photosynthesis in canola, and also was the intersection of "source and reservoir" to yield formation (Diepenbrock 2000;Momoh and Zhou 2001;Hamzei and Soltani 2012;Shabani et al, 2014;Fochesatto et al, 2016). Owing to the influence of plant height, angle and orientation between leaves, branches, pods and main stem, length of leaves and branches and other factors, the photosynthetic area coefficient and light distribution in plant canopy were very different, resulting in the different photosynthetic efficiency of the canopy consequently (Han et al, 2014;Cui et al, 2015;Chang et al, 2016).…”
Section: Evaluating the High Light Use Efficiency Of Canola Varietiesmentioning
confidence: 94%
“…Therefore, it is an urgent problem for breeders and cultivators to find a suitable way to improve the yield of canola. At present, the actual light use efficiency of canola is only 0.615%-1.056% (Hamzei and Soltani 2012;Fochesatto et al, 2016). If the light use efficiency is increased by 0.1 percentage point, the yield can be increased by 20%-25% or more (Purcell et al, 2002;Soleymani 2017).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation